2021
DOI: 10.1002/smll.202103003
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Responsive Hydrogel as an Angiogenesis Inhibition Agent for Tumor Microenvironment Reprogramming

Abstract: The data that support the findings of this study are available from the corresponding author upon reasonable request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Compared to the first near-infrared (NIR-I) window (from 750 to 1,000 nm), the second near-infrared (NIR-II) window (from 1,000 to 1,350 nm) for photothermal therapy exhibits inherent advantages of the deeper tissue-penetration, lower light scattering and higher maximum permissible exposure ( Lin et al, 2017 ; Liu Y. et al, 2019 ; Liu G. et al, 2019 ; Tian et al, 2021 ). Thus, many attempts have been contributed to developing new NIR-II-triggered photothermal nanoagents with satisfactory PTT efficacy through oxygen vacancy engineering ( Han et al, 2018 ; Yin et al, 2018 ; Zhao et al, 2021 ; Zhou Z. et al, 2021 ). For example, Chen et al ( Han et al, 2018 ) created an oxygen-defective TiO 2− x layer onto the surface of TiO 2 nanosemiconductors through a facile aluminum-reduction strategy, thus constructing a crystalline-disordered core-shell structure (TiO 2 @TiO 2− x ) with black color.…”
Section: Vacancy Defective Nanomaterials-enhanced Phototherapy and Mu...mentioning
confidence: 99%
“…Compared to the first near-infrared (NIR-I) window (from 750 to 1,000 nm), the second near-infrared (NIR-II) window (from 1,000 to 1,350 nm) for photothermal therapy exhibits inherent advantages of the deeper tissue-penetration, lower light scattering and higher maximum permissible exposure ( Lin et al, 2017 ; Liu Y. et al, 2019 ; Liu G. et al, 2019 ; Tian et al, 2021 ). Thus, many attempts have been contributed to developing new NIR-II-triggered photothermal nanoagents with satisfactory PTT efficacy through oxygen vacancy engineering ( Han et al, 2018 ; Yin et al, 2018 ; Zhao et al, 2021 ; Zhou Z. et al, 2021 ). For example, Chen et al ( Han et al, 2018 ) created an oxygen-defective TiO 2− x layer onto the surface of TiO 2 nanosemiconductors through a facile aluminum-reduction strategy, thus constructing a crystalline-disordered core-shell structure (TiO 2 @TiO 2− x ) with black color.…”
Section: Vacancy Defective Nanomaterials-enhanced Phototherapy and Mu...mentioning
confidence: 99%
“…Secondly, hydrogel can realize controllable drug releasing [ 49 51 ]. Hydrogels can respond to various stimuli [ 52 ], for example, light [ 53 ], near infrared light (NIR) [ 54 56 ], temperature [ 57 , 58 ], pH [ 59 ], magnetic field [ 60 ], enzymes [ 61 ], ionic strength and electric field. The controlled release of drugs can be realized by virtue of the reversible expansion and contraction properties of hydrogels under specific stimulation conditions to fix the size of gel grids.…”
Section: Introductionmentioning
confidence: 99%
“…intravenous injection) have a series of problems such as low efficiency of nanomaterials reaching tumor tissue, premature leakage of cargo, and profound toxicity caused by the long-term existence of the carrier in the body (24)(25)(26). Numerous studies have shown that hydrogel delivery system can prolong the sustained release time of materials, prolong the effect of materials, and improve the effect of tumor treatment (27). Adding nanomaterials into hydrogel solution by diffusion or grafting to hydrogel materials can directly hit the lesion site by implantation or injection to achieve the effect of local slow-release drugs (28,29).…”
Section: Introductionmentioning
confidence: 99%